Flask framework cookbook : enhance your Flask skills with advanced techniques and build dynamic, responsive web applications - Aggarwal, Shalabh (Packt Publishing Ltd., 2023)
Design and deploy robust state-of-the-art web applications using Flask 2.x and Python 3 frameworks and libraries for streamlined development and optimal performance Purchase of the print or Kindle book includes a free PDF eBook Key Features A practical and rich companion guide for web developers, offering real-world situations and use cases to learn Flask Get the most out of the powerful Flask framework while preserving the flexibility of your design choices Write cleaner, testable, and maintainable code with the help of sample apps Book Description Discover what makes Flask, the lightweight Python web framework, popular, as you delve into its modular design that enables the development of scalable web apps. With this practical guide, you'll explore modern solutions, recommended design patterns, and best practices for Flask web development. Updated to the latest version of Flask and Python, this third edition of the Flask Framework Cookbook moves away from the outdated libraries, updates content to incorporate new coding patterns, and introduces recipes for the latest tools. You'll explore different ways to integrate with GPT to build AI-ready Flask applications. The book starts with an exploration of Flask application configurations and then guides you through working with templates and understanding the ORM and view layers. You'll also be able to write an admin interface and get to grips with testing using the factory pattern, debugging, and logging errors. Then you'll discover different ways of using Flask to create, deploy, and manage microservices using AWS, GCP, and Kubernetes. Finally, you'll gain insights into various deployment and post-deployment techniques for platforms such as Apache, Tornado, and Datadog. By the end of this book, you'll have acquired the knowledge necessary to write Flask applications that cater to a wide range of use cases in the best possible way and scale them using standard industry practices. What you will learn Explore advanced templating and data modeling techniques Discover effective debugging, logging, and error-handling techniques in Flask Work with different types of databases, including RDBMS and NoSQL Integrate Flask with different technologies such as Redis, Sentry, and Datadog Deploy and package Flask applications with Docker and Kubernetes Integrate GPT with your Flask application to build future-ready platforms Implement continuous integration and continuous deployment (CI/CD) to ensure efficient and consistent updates to your Flask web applications Who this book is for If you are a web developer seeking to expand your knowledge of developing scalable and production-ready applications in Flask, this is the book for you. It is also highly valuable if you are already aware of Flask's major extensions and want to leverage them for better application development. This book will come handy as a quick reference for specific topic on Flask, its popular extensions, or specific use cases. It assumes basic Python programming experience, as well as familiarity with web development and related terminology.